The Role of Seed Banks in Resisting Agricultural and Ecological Degradation: The Case of Portugal - Guedes, M.; Ferreiro, Maria de Fátima; Proença, Vânia (5th International Conference Social and Solidarity Economy and the Commons, 2025)
This research evaluates the role of three Portuguese seed banks—the Portuguese Plant Germplasm Bank (BPGV), the Seed Bank of the National Museum of Natural History and Science (MUHNAC), and the Colher para Semear network—in regenerating agrobiodiversity and advancing food sovereignty. Framed by political-ecology and institutional-economics theories, the study tackles three interlinked questions: (1) how community-driven seed practices (saving, exchange, multiplication) enhance ecological resilience and empower local food systems; (2) what legal-institutional obstacles arise from prevailing regimes such as EU seed legislation and how they constrain bank operations; and (3) how the banks implement commons-based governance, stewardship, and reciprocal knowledge networks to sustain conservation and systemic resilience. Employing a transdisciplinary methodology that merges legal-document analysis with semi-structured interviews of the banks’ coordinators, the findings reveal a pronounced mismatch between the homogenising, variety-uniformity emphasis of current intellectual-property frameworks and the banks’ focus on long-term ecological and cultural regeneration. Legal ambiguities, governance asymmetries, and institutional lock-ins emerge as major barriers to transformative food systems. The study argues that re-politicising seed conservation and recognising seeds as material-cultural commons are essential steps toward building resilient, sovereign, and livable futures in Portugal.